2021
DOI: 10.1136/bmjgast-2021-000729
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ‘new-onset’ constipation and associated factors during lockdown due to the COVID-19 pandemic

Abstract: ObjectiveA minimum of physical activity and low liquid intake are factors that have been associated with constipation. The health emergency brought on by the COVID-19 pandemic has resulted in adopting behaviour, such as sheltering-in-place (less mobility) and dietary changes, creating a scenario we believe to be an adequate model for examining the appearance of symptoms of constipation and its associated factors.DesignA cross-sectional and descriptive study was conducted on an open population, applying an elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Kayaoglu et al 31 revealed a decrease in CIC prevalence after social isolation of 15.1 to 1.3% in the general population. Remes-Troche et al, 32 on the other hand, evidenced in 1.110 volunteers the appearance of complains related to constipation in 25% after 4 weeks of social isolation.…”
Section: Discussionmentioning
confidence: 93%
“…Kayaoglu et al 31 revealed a decrease in CIC prevalence after social isolation of 15.1 to 1.3% in the general population. Remes-Troche et al, 32 on the other hand, evidenced in 1.110 volunteers the appearance of complains related to constipation in 25% after 4 weeks of social isolation.…”
Section: Discussionmentioning
confidence: 93%
“…That study however did not use validated criteria to distinguish habitual/intermittent constipation from chronic FC which reiterates the importance of making that distinction when comparing prevalence. 32 …”
Section: Discussionmentioning
confidence: 99%
“…That study however did not use validated criteria to distinguish habitual/intermittent constipation from chronic FC which reiterates the importance of making that distinction when comparing prevalence. 32 Patients with FAPDs and FGIDs frequently exhibit features of more than one disorder simultaneously since criteria for FAPD subcategories do tend to overlap. 4,33,34 We redemonstrated in the present study that the majority of our FAPDs cases did meet criteria for at least two disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Esto probablemente ha traído consecuencias para el hábito alimentario de los ciudadanos, quienes han recurrido al aumento de alimentos ricos en carbohidratos y grasas como una forma de generar la sensación de reconforte (75) . En un estudio realizado por Remes-Troche y colaboradores (76) con 678 pacientes en los que se evaluó la incidencia de síntomas de estreñimiento durante el confinamiento implementado para contener la propagación de COVID-19 en México, se encontró que este cambio en los hábitos alimentarios aumentó las cifras de estreñimiento de "nueva aparición", una disminución significativa de la cantidad de deposiciones y heces más duras durante el confinamiento.…”
Section: Aumento Del Miedo Y La Ansiedad Que Causa Prácticas De Alime...unclassified